Pelaksanaan Ekstrakurikuler Kepramukaan untuk Menanamkan Karakter Peserta Didik di SDS 117 Islam Terpadu Adnani - Laila Safitri; Rohman; Anni Kholilah; Rahmayani; Saridona; Nur Azizah; Khoirunnisah; Nabilah Ayu; Diana Rizki (Ambacang: Jurnal Inovasi Pengabdian Masyarakat, 2025)
Education plays a central role in shaping the character of the nation, and one effective method in building the character of students is through extracurricular activities of Scouting. This paper discusses the implementation of scouting activities at SDS 117 Islam Terpadu Adnani as a form of devotion in shaping the character of students. The activities lasted for three days, including hiking, skills competitions, joint worship, and various group activities aimed at instilling the values ​​of discipline, cooperation, leadership, and social concern. The results of the activities showed that the direct experience-based approach through Scouting was effective in improving scouting skills, physical endurance, and morality of students. The integration of religious and social values ​​in this activity also had a positive impact in shaping individuals who were more responsible, disciplined, and had a strong leadership spirit. Thus, Scouting activities can be used as a model for sustainable character learning in the education system.